Filling in the Doughnut? Police Operational Discretion and the Law in Australia. (1st December 2014) - Clark, David
ABSTRACT: This paper considers the rise of administrative accountability of police discretionary decisions in Australia. The expansion of review has been the result of new institutions such as police integrity units and police complaints bodies, as well as through administrative law remedies. In particular the paper shows that judicial review in the Australian federal system has increased surveillance over operational decision-making and the limits to that review. The paper concludes that the nature of police decision-making at the command level may be subject to scrutiny, but that street level operations remain mostly out of the reach of the courts.